1976
DOI: 10.6028/nbs.ir.76-1072
|View full text |Cite
|
Sign up to set email alerts
|

Back-up report for the proposed standard for the flammability of general wearing apparel

Abstract: A "Proposed Standard for the Flairanability of General WearingApparel" was submitted to the Consumer Product Safety Commission in February 1976. This report discusses the reasons for the choices of experimental arrangement for the flammability test and the choices of pass-fail criteria.The specimen is cylindrical, to simulate a garment, and to eliminate framed specimens which often burn differently from garments. Criteria for the fire hazard of fabrics are the time to ignite with a specified gas flame and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…(2.22-cm) methane flame for 3 s from a No. 18 gauge hypodermic needle as specified in the MAFT [1] apparatus. 01 was determined in the usual manner [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2.22-cm) methane flame for 3 s from a No. 18 gauge hypodermic needle as specified in the MAFT [1] apparatus. 01 was determined in the usual manner [12].…”
Section: Introductionmentioning
confidence: 99%
“…cabinet. The cabinet was assembled in accord- [1]. Fabric specimens were burned in the horizontal position and in normal atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the flammability of the fabric was related to garment size, coverage, and design criteria as is most appropriate. These were submitted to CPSC for consideration [17]. However, the project was discontinued by CPSC at this point and never revived.…”
Section: Discussionmentioning
confidence: 99%
“…7, the greater air supply can increase the rate of flame spread. Krasny and co-workersl79 18 have shown that a loosely fitting configuration which covers more than half of the body results in more serious burns because of the absence of fire stops.…”
Section: The Classification and Labelling Of Children's Nightwearmentioning
confidence: 99%